Design and simulation of rectangular patch antenna arrays with high bandwidth for 2.4 GHz ISM band applications - Kymbat Kopbay; Madiyar Nurgaliyev; Ahmet Saymbetov; Nurzhigit Kuttybay; Askhat Bolatbek; Sayat Orynbassar; Batyrbek Zholamanov (TELKOMNIKA (Telecommunication Computing Electronics and Control), 2025)
Ongoing advancements in microstrip patch antenna (MPA) development research is driven by its compact size, cost-effectiveness and ease of fabrication. This paper presents a flexible design of patch antenna array (PAA) to address bandwidth (BW) limitations within the 2.4 GHz industrial, scientific, and medical (ISM) band, where narrow BW is a common challenge. To explore the effectiveness of different array configurations, we designed and evaluated 1×2, 2×2, and 2×4 element rectangular PAA, employing a quarter-wave transformer (QWT) method and parallel scheme for connecting patches. By utilizing Ansys high frequency structure simulator (HFSS) as the modeling environment, we conducted extensive simulations to refine the antenna parameters and achieve the most optimal MPA prototype. Our investigation demonstrates sufficiently good results, including BWs of 290 MHz and 210 MHz for 2×2 and 2×4 PAAs respectively, which account for 8.75% and 12% of the total value. The parameter return loss (RL) (S_11) reached -51dB for single-element patch antenna (SPA) and -37.5 dB for 8-element PAA, that shows an ideal impedance matching. In addition, the designed 2×4 PAA exhibited impressive performance metrics, accounting for 9.17 dB in gain, 13 dBi in directivity, and voltage standing wave ratio (VSWR) maintained below 0.5, ensuring excellent signal transmission and reception.